HAK ASASI MANUSIA DALAM KAJIAN GENDER ANALISIS BIBLIOMETRIK TENTANG KESETARAAN DAN DISKRIMINASI - Muhammad Holid (Sekolah Tinggi Ilmu Syariah Abu Zairi Bondowoso, 2024)
This research method provides a comprehensive bibliometric analysis of the human rights research landscape in gender studies, specifically focusing on the topics of equality and discrimination. Using data collection, analysis and visualization techniques, this research aims to identify key research themes, trends, influential authors and publications, as well as knowledge gaps within the field. This analysis uses VOSviewer software for network visualization, which allows mapping of thematic groups and interconnections. These findings offer valuable insights to inform policy decisions, guide future research, and encourage interdisciplinary collaboration in achieving gender equality and the advancement of human rights.